CYTOTOXIC EFFECT OF METHANOL EXTRACTS OF SEAWEEDS - B.VASUDEVA RAO; M. BOOMINATHAN (International Journal of Pharma and Bio Sciences, 2016)
Anticancer activity of marine macro algae (seaweeds) Ulothrixflacca, Ulva fasciata and Caulerpataxifolia against an invitroswiss albino neuroblastoma model (N2a) cell line was studied. During the present investigation crude methanol extracts of seaweeds were prepared using soxhlet apparatus. Crude extracts were dissolved in DMSO. In vitro anticancer activity of seaweeds at various concentrations (10–5000 ng/ml) was studied against the chosen cell lines using MTT assay (3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide, a yellow tetrazole). All the three extracts showed anticancer activity with excess LDH release and ROS production which activated structural injury to mitochondrial membrane. Of which Methanolic extract of Caulerpataxifolia (275 ng/ml) has shown greater IC50 value than Ulothrixflaccaand Ulva fasciatawhich showed 500ng/ml and 400ng/ml respectively, indicating greater anticancer activity. The present study indicates that the methanolic seaweed extracts were effective in the production of ROS-dependent mitochondrial damage-induced cytotoxicity in N2a cells.